Experimental Validation of Metaheuristic Optimized Fractional-Order PID Control for a Rotary Inverted Pendulum - Abut, Tayfun (Ieee-Inst Electrical Electronics Engineers Inc, 2026)
The rotary inverted pendulum (RIP) system is a difficult system to control due to its underactuated and unstable structure. This study aimed to maintain the pendulum arm in the upright equilibrium position and suppress oscillations while improving the stabilization performance of the rotary arm. In this paper, a model of the RIP system was created, and Fractional Order Proportional-Integral-Derivative (FOPID) controllers combined with an integral anti-windup technique were proposed for the robust stabilization and control of the RIP system using metaheuristic optimization techniques. To enhance the performance of FOPID control methods, the parameters of the controllers were determined using Starfish Optimization Algorithm (SFOA), Harris Hawks Optimization (HHO), and Grey Wolf Optimization (GWO) algorithms, respectively. The optimized controller parameters were implemented on the RIP system in real time, and the results were evaluated numerically and experimentally. Using the settling time performance, the techniques were analyzed in comparison with each other and the studies in the literature. The examination of the proposed method (SFOA-FOPID) indicates an improvement of 22.5% in settling time and 39.5% in error compared to the GWO-FOPID approach. The study demonstrates the effectiveness of the metaheuristic optimization-based FOPID approaches for RIP systems.
Keywords: Rotary Inverted Pendulum; Real-Time Control; Fractional Order Proportional-Integral-Derivative; Starfish Optimization Algorithm; Harris Hawks Optimization; Grey Wolf Optimization; Rotary Inverted Pendulum; Real-Time Control; Fractional Order Proportional-Integral-Derivative; Starfish Optimization Algorithm; Harris Hawks Optimization; Grey Wolf Optimization